Reciprocal regulation between Acinetobacter baumannii and Enterobacter cloacae AdeR homologs: implications for antimicrobial resistance and pathogenesis - Marc Gaona; Jordi Corral; Miquel Sánchez−Osuna; Susana Campoy; Jordi Barbé; María Pérez-Varela; Jesús Aranda (PLoS ONE, 2025)
Acinetobacter baumannii and Enterobacter cloacae are phylogenetically distant Gram−negative bacterial pathogens that represent significant challenges in healthcare settings due to their remarkable ability to acquire antimicrobial resistance. This study investigates one of the most important efflux pump systems in A. baumannii, AdeABC−AdeRS, and identifies homologous components in E. cloacae. By constructing isogenic knockout mutants, we show that the AdeB pump component and the AdeR regulator are significant for antimicrobial resistance and pathogenicity in A. baumannii. Through in silico predictions, we identify homologs of AdeB and AdeR (ECL_01758 and ECL_01761, respectively) in E. cloacae. Notably, we demonstrate that while the inactivation of the E. cloacae gene encoding the AdeB protein does not impact on pathogenesis and only alters colistin susceptibility, a knockout mutant of the gene encoding the AdeR regulator significantly affects susceptibility to various antimicrobial classes, motility, and virulence. Additionally, we demonstrate that the AdeR regulators of A. baumannii and E. cloacae can functionally substitute for each other both in vitro and in vivo conditions. Electrophoretic mobility shift assays reveal that these regulators are capable of binding to the promoter regions of each other’s species, where similar DNA motifs are present. Furthermore, cross−complementation tests show that the affected phenotypes in each species can be restored interchangeably. Moreover, phylogenomic analysis of previously published E.cloacae genomes and reconstructrion of ancestral states through the phylogenetic trees of the adeB and adeR genes suggest that these homologs are more likely derived from a common ancestor rather than through recent horizontal gene transfer. The findings of this work highlight that conserved regulatory functions concerning efflux pump expression can be maintained across species despite evolutionary divergence and open new perspectives for the control of bacterial infections.